Stuck between surplus and shortage: demand for skills in the Russian industry - Vladimir Gimpelson; Rostislav Kapelyushnikov; Anna Lukiyanova (Institute for the Study of Labor (IZA), 2009)
In order to remain competitive, firms need to keep the quantity and composition of jobs close to the optimal for their given output. Since the beginning of the transition period, Russian industrial firms have been widely reporting that the quantity and composition of hired labor is far from being close to optimal. This paper discusses what kinds of firms in the Russian manufacturing sector are not able to optimize their employment and why. Do they suffer from a labor shortage induced by rapid growth, or are they still struggling with employment overhang? What are the occupations and skills in which there is a supposed surplus or shortage? What factors affect the probability that a firm will report non-optimal employment and be unable to solve this difficulty? Where is the labor excess/shortage concentrated and what makes it persistent? Finally, we discuss the costs of non-optimal employment. The analysis presented in this article is based on the data from a large-scale survey of Russian manufacturing firms.
urn:nbn:de:101:1-20090123109
Keywords: J23; J24; 330; Labour shortage; skills; training; transition economies; Russia; Arbeitsnachfrage; Qualifikation; Berufsbedarf; Verarbeitendes Gewerbe; Übergangswirtschaft; Russland